Envisioning motherhood: Mental‐state language in caregiving narratives across the perinatal period. Issue 2 (2nd March 2023) - Rutherford, Helena J. V.; Yatziv, Tal; Vess, Matthew; Brooker, Rebecca J
Abstract: Nancy Suchman's work highlighted the fundamental role of maternal mentalization in maternal addiction, mental health, and caregiving challenges. In this study, we aimed to examine the role of mental‐state language (MSL) as a measure of mentalization in prenatal and postnatal narratives and their sentiment in a sample of 91 primarily White mothers from the western United States, followed from the second trimester of pregnancy, through the third trimester, to 4 months postpartum. Specifically, we investigated the use of affective and cognitive MSL in prenatal narratives when mothers visualized caring for their baby and postnatal narratives when mothers compared their prenatal visualization to the current caregiving reality. Results indicated moderate consistency in MSL between the second and third trimesters, but prenatal and postnatal MSL was not significantly correlated. Across all time points, higher use of MSL was related to more positive sentiment, indicating an association between mentalization and positive caregiving representations across the perinatal period. Women used more affective than cognitive MSL in prenatal imagination of caregiving, but this pattern was reversed in their postpartum reflection. Implications on assessing parental mentalization prenatally and considering the relative dominance of affective and cognitive mentalizing are discussed while considering study limitations. Resumen: El trabajo de Nancy Suchman subrayó el papel fundamental de la mentalización maternal en la adicción materna, la salud mental y los retos de la prestación de cuidado. En este estudio, nos propusimos examinar el papel del lenguaje del estado mental como una medida de mentalización en las narrativas pre‐ y postnatales y su sentimiento en un grupo muestra de 91 madres primariamente blancas del oeste de los Estados Unidos, a quienes se les dio seguimiento a partir del segundo trimestre de embarazo, a través del tercer trimestre, hasta 4 meses después del parto. Específicamente, investigamos el uso de lenguaje del estado mental afectivo y cognitivo en las narrativas prenatales cuando las madres visualizaban el cuidado de su bebé, y las narrativas postnatales cuando las madres comparaban su visualización prenatal con la presente realidad de prestación de cuidado. Los resultados indicaron una consistencia moderada en el lenguaje del estado mental entre el segundo y tercer trimestres, pero el lenguaje del estado mental prenatal y postnatal no fue significativamente correlacionado. A los largo de todos los punto temporales, el más alto uso del lenguaje del estado mental se relacionó con un más positivo sentimiento, indicando así una asociación entre la mentalización y las representaciones positivas de la prestación de cuidado a lo largo del período perinatal. Las mujeres usaron más lenguaje del estado mental afectivo que cognitivo en la imaginación prenatal de la prestación de cuidado, pero este patrón se invirtió en sus reflexiones después del parto. Se discuten las implicaciones sobre el tener acceso a la mentalización del progenitor prenatalmente y considerar el relativo dominio del mentalizarse en lo afectivo y cognitivo, al tiempo que se consideran las limitaciones del estudio. Résumé: Le travail de Nancy Suchman a mis en lumière le rôle fondamental de la mentalisation maternelle dans l'addiction maternelle, la santé mentale et les défis de la prestation de soins. Dans cette étude nous nous sommes donné pour but d'examiner le rôle du langage d'état mental en tant que mesure de la mentalisation dans les narrations prénatales et postnatales et leur sentiment chez un échantillon de 91 mères dans l'ensemble blanches vivant dans l'ouest des Etats‐Unis d'Amériques, et suivies du second trimestre de la grossesse, durant le troisième trimestre jusqu'à 4 mois après la naissance. Plus particulièrement nous nous sommes penchés sur l'utilisation du langage d'état mental affectif et cognitif dans des narrations prénatales lorsque les mères visualisaient les soins à leur bébé, et les narrations postnatales lorsque les mères comparaient leur visualisation prénatale à la réalité actuelle des soins au bébé. Les résultats ont indiqué une cohérence modérée dans le langage d'état mental entre les second et troisième trimestres mais le langage d'état mental prénatal et postnatal n'était pas significativement corrélé. Au travers de tous les points temporels l'utilisation plus grande de langage d'état mental était liée à un sentiment plus positif, indiquant un lien entre la mentalisation et les représentations positives des soins au travers de la période périnatale. Les femmes ont utilisé un langage d'état mentale plus affectif que cognitif dans l'imagination prénatale des soins, mais ce schéma était renversé dans leur réflexion postpartum. Les implications pour l'évaluation de la mentalisation parentale avant la naissance et pour la considération de la domination relative de la mentalisation affective et cognitive sont discutées, tout en considérant les limites de l'étude. Zusammenfassung: Mutterschaft in der Vorstellung: Die Sprache bezüglich mentaler Zustände in Betreuungsnarrativen während der Perinatalperiode Die Arbeit von Nancy Suchman hat die fundamentale Rolle der mütterlichen Mentalisierung bei mütterlicher Sucht, psychischer Gesundheit und Betreuungsherausforderungen hervorgehoben. In dieser Studie untersuchten wir die Rolle von Sprache bezüglich mentaler Zustände als Maß für Mentalisierung in pränatalen und postnatalen Narrativen und deren Stimmungslage. Die Untersuchung erfolgte in einer Stichprobe von 91 vorwiegend weißen Müttern aus dem Westen der USA, die vom zweiten Trimester der Schwangerschaft über das dritte Trimester bis vier Monate nach der Geburt beobachtet wurden. Insbesondere untersuchten wir die Verwendung von Sprache bezüglich affektiver und kognitiver mentaler Zustände. Gegenstand der Untersuchung waren pränatalen Narrative, in denen sich die Mütter die Betreuung ihres Babys vorstellten, sowie postnatale Narrative, in denen die Mütter ihre pränatalen Vorstellungen mit der aktuellen Betreuungsrealität verglichen. Die Ergebnisse zeigten eine moderate Übereinstimmung in der Sprache bezüglich mentaler Zustände zwischen dem zweiten und dritten Trimester. Die Sprache bezüglich mentaler Zustände zwischen den pränatalen und postnatalen Messzeitpunkten war allerdings nicht signifikant korreliert. Über alle Messzeitpunkte hinweg war ein höherer Gebrauch von Sprache bezüglich mentaler Zustände mit einer positiveren Stimmungslage verbunden, was auf einen Zusammenhang zwischen Mentalisierung und positiven Betreuungsrepräsentationen während der gesamten Perinatalperiode hinweist. Zu pränatalen Messzeitpunkten verwendeten die Frauen mehr affektive als kognitive Mentalisierungssprache, wenn sie sich die Betreuung ihres Babys vorstellten. Dieses Muster kehrte sich allerdings in der postpartalen Reflexion um. Implikationen für die pränatale Beurteilung elterlicher Mentalisierung und die Berücksichtigung der relativen Dominanz von affektivem und kognitivem Mentalisieren werden unter Einbezug der Studienlimitationen erörtert. 抄録: 母であることを思い描くこと 周産期のお世話についてのナラティブにおける心理状態を表すことば Nancy Suchmanの研究は、母親の依存症、精神保健、子育ての課題における母親のメンタライゼーションの基本的な役割に注目した。本研究では、アメリカ西部の主に白人の母親91名を対象に、妊娠第2期から第3期を経て産後4ヶ月まで追跡調査し、産前産後のナラティブにおけるメンタライゼーションとその心情の指標としての心理状態を表すことばの役割を検討することを目的とした。具体的には、母親が自分の子どもの世話することを思い浮かべる時の産前の語りの中や、母親が産前の想像と今の現実の子育てを比較した時の産後の語りの中で、情緒的で認知的な心理状態を表す言語の使用状況を調査した。その結果、妊娠第2期と第3期の精神状態を表すことばには中程度の一貫性が認められたが、産前と産後の心理状態を表すことばには有意な相関は認められなかった。全ての時期において、心理状態を表すことばの使用が多いほど、より肯定的な感情と関連しており、周産期を通じてメンタライゼーションと肯定的な子育て表象との関連が示唆された。女性は、出生前の想像では、認知的な心理状態を表すことばよりも感情的な精神状態を表すことばを多く使用していたが、このパターンは産後の振り返りでは逆転していた。本研究の限界を考慮しつつ、出生前に親のメンタライゼーションを評価し、感情的メンタライゼーションと認知的メンタライゼーションの相対的優位性を考慮することの意義について議論した。 摘要: Nancy Suchman的工作强调了母亲心智化在母亲药物成瘾、心理健康和护理挑战中的基础性作用。在本研究中, 我们的目的是在91名来自美国西部的白人母亲样本中, 从妊娠中期到妊娠晚期, 再到产后4个月, 考察其心理状态语言在产前和产后叙事及其情感中作为心智化的一种衡量标准的作用。具体而言, 我们调查了当母亲想象照顾婴儿时, 情感和认知心理状态语言在产前叙事中的使用, 以及当母亲将其产前想象与当前护理现实进行比较时, 在产后叙事中的使用。结果表明, 妊娠中期和妊娠晚期心理状态语言有一定的一致性, 而产前和产后心理状态语言无显著相关性。在所有时间点上, 心理状态语言的使用率越高, 情绪越积极, 这表明在围产期, 心智化和积极的护理表现之间存在关联。母亲在产前护理想象中使用的情感语言多于认知心理状态语言, 而在产后反思中刚好相反。在考虑研究局限性的同时, 对产前评估父母心智化, 以及思考情感和认知心智化的相对优势进行了讨论。 ملخص: تصور الأمومة: لغة الحالة العقلية في روايات تقديم الرعاية خلال فترة ما حول الولادة سلط عمل نانسي سوشمان الضوء على الدور الأساسي للحالات العقلية الأمومية في إدمان الأمهات والصحة النفسية وتحديات تقديم الرعاية. في هذه الدراسة، هدفنا إلى فحص دور لغة الحالة العقلية كمقياس للتصورات العقلية في روايات ما قبل الولادة وما بعدها ومشاعرهم في عينة من 91 من الأمهات البيض بشكل أساسي من غرب الولايات المتحدة، والذين تم تتبعهم من الثلث الثاني من الحمل، حتى الثلث الثالث من الحمل، إلى 4 أشهر بعد الولادة. على وجه التحديد، قامت الدراسة بالتحقيق في استخدام لغة الحالة العقلية العاطفية والمعرفية في روايات ما قبل الولادة عندما تصورت الأمهات رعاية أطفالهن، وروايات ما بعد الولادة عندما قارنت الأمهات تصورهن قبل الولادة بواقع تقديم الرعاية الحالي. أشارت النتائج إلى اتساق معتدل في لغة الحالة العقلية بين الثلث الثاني والثالث، لكن لغة الحالة العقلية قبل الولادة وبعدها لم تكن مرتبطة بشكل كبير. في جميع النقاط الزمنية، كان الاستخدام الأعلى للغة الحالة العقلية مرتبطًا بمشاعر أكثر إيجابية، مما يشير إلى وجود ارتباط بين التمثيل العقلي وتمثيلات تقديم الرعاية الإيجابية عبر فترة ما حول الولادة. استخدمت النساء لغة أكثر عاطفية من لغة الحالة العقلية المعرفية في تخيلاتهم قبل الولادة عن تقديم الرعاية، ولكن تم عكس هذا النمط في تأمل ما بعد الولادة. تناقش الدراسة التطبيقات المترتبة على تقييم الحالات العقلية للوالدين قبل الولادة والنظر في الهيمنة النسبية للحالات العاطفية والمعرفية، مع الأخذ في الاعتبار قيود ومحدودية الدراسة.